Scrabble : Play Like a Champion - Simmons, Allan (Bishopbriggs, Glasgow HarperCollins Publishers, 2010)
Keen, eager and fiercely competitive when it comes to Scrabble? This book will help you get into the mind of one of the UK's best-ever Scrabble players, so that you can think like a champion and beat everyone you play
Keywords: Scrabble (Game)